SOCIO-PERSONALOGICAL FACTORS AS DETERMINANTS OF ANTISOCIAL BEHAVIOURS AMONG ADOLESCENTS IN IKENNE, OGUN STATE - Williams, Taiwo M.; Aderanti, Ruth A.; Womiloju, Ayodele (European Scientific Journal, ESJ, 2015)
The dynamic relationship between individual and social factors and their connection with adolescents’ anti-social behaviour have been examined using a descriptive survey design. Three schools were purposively selected in Ikenne local Government and Two hundred and thirty-one Senior Secondary School students from these schools participated in the study. Three instruments namely, Adolescent Self-Regulatory Inventory (ASRI), Monitoring the Future Study and Delinquent Subscale of the Child Behaviour Checklist – Youth Self Report were adapted to examine the effect of independent variables on dependent variable. Reliability values of 0.78, 0.65 and 0.75 respectively were obtained for the instrument. Multiple regression and independent t-test were used to test the three hypotheses postulated. The results show significant joint and relative contribution of the independent variables on adolescents’ anti-social behaviour . The moderating effect of gender on self-control was also significant while gender did not moderate the effect of social skill on antisocial behaviour. It was then concluded that the combination of self-control and social skills can help reduce the antisocial behaviours displayed by adolescents. Implications for counseling have been outlined in the body of the work.